Half-life extension and non-human primate pharmacokinetic safety studies of i-body AD-114 targeting human CXCR4. Issue 7 (3rd October 2019) - Griffiths, Katherine; Binder, Uli; McDowell, William; Tommasi, Rita; Frigerio, Mark; Darby, William G.; Hosking, Chris G.; Renaud, Lionel; Machacek, Matthias; Lloyd, Peter; Skerra, Arne; Foley, Michael
ABSTRACT: Single domain antibodies that combine antigen specificity with high tissue penetration are an attractive alternative to conventional antibodies. However, rapid clearance from the bloodstream owing to their small size can be a limitation of therapeutic single domain antibodies. Here, we describe and evaluate the conjugation of a single domain i-body, AD-114, which targets CXCR4, to a panel of half-life extension technologies including a human serum albumin-binding peptide, linear and branched PEG, and PASylation (PA600). The conjugates were assessed in murine, rat and cynomolgus monkey pharmacokinetic studies and showed that the branched PEG was most effective at extending circulating half-life in mice; however, manufacturing limitations of PEGylated test material precluded scale-up and assessment in larger animals. PA600, by comparison, was amenable to scale-up and afforded considerable half-life improvements in mice, rats and cynomolgus monkeys. In mice, the circulating half-life of AD-114 was extended from 0.18 h to 7.77 h following conjugation to PA600, and in cynomolgus monkeys, the circulating half-life of AD-114-PA600 was 24.27 h. AD-114-PA600 was well tolerated in cynomolgus monkeys at dose rates up to 100 mg/kg with no mortalities or drug-related clinical signs.